Genomic and transcriptomics analysis reveal putative secreted proteins expressed of Pasteurella multocida during 18β-glycyrrhetinic acid treatment - Wu, Zhongyuan; Zhang, Yuhan; Wang, Luyao; Mei, Meng; Qiu, Yinsheng; Liu, Yu; Fu, Shulin; Xiong, Jianglin; Lu, Qirong; Guo, Pu (Frontiers in Veterinary Science, 2024)
Pasteurella multocida is a gram-negative opportunistic pathogen that can infect both domestic animals and humans, leading to large economic losses to the livestock industry. 18β-Glycyrrhetinic acid, the main active component of Glycyrrhiza glabra L., has antibacterial properties. However, the virulence factors (especially the secreted proteins with eukaryotic-like domains) and pathogenesis of P. multocida and the regulatory effect of 18β-glycyrrhetinic acid have not been fully elucidated. This study focused on predicting secreted proteins with eukaryotic-like domains in P. multocida and examining the antibacterial effects of 18β-glycyrrhetinic acid on P. multocida. We combined transcriptomics analysis and in silico approaches to explore virulence factors in the P. multocida HB03 genome and identified 40 secreted proteins with eukaryotic-like domains regulated by 18β-glycyrrhetinic acid. Quantitative real-time polymerase chain reaction (qPCR) showed that compared with the P. multocida group, 18β-glycyrrhetinic acid significantly reduced the expression of aceF, gdhA, hpaG, and sel1L and increased the expression of galT and xynC, which was consistent with the transcriptomic data. Combining these qPCR results with the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes annotation results showed that 18β-glycyrrhetinic acid interfered with bacterial energy metabolism and host interactions by regulating the expression of virulence factors in P. multocida. Moreover, molecular docking revealed that 18β-glycyrrhetinic acid had the potential to target aceF and hpaG, thus regulating the activity of secreted proteins. Our findings indicate that predicting the secreted proteins with eukaryotic-like domains in P. multocida and elucidating the regulatory effect of 18β-glycyrrhetinic acid provides a theoretical basis for the prevention and control of P. multocida infection and the development of alternative antibiotic therapies.